2017
DOI: 10.5897/jphe2017.0928
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory symptoms and associated factors among solid waste collectors in Yeka Sub City, Addis Ababa, Ethiopia

Abstract: Respiratory symptoms are frequently manifested among solid waste collectors. They are suffering from respiratory diseases because of frequent exposure to waste materials containing pathogenic materials and chemicals hazards for human being. Cross-sectional study was carried out to assess prevalence of respiratory symptoms and associated factors among solid waste workers in Yeka sub city, Addis Ababa from March to April, 2016. The sub city has a total of 13 woredas. All woredas had different number of unions or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Street sweepers with a history of respiratory illness are more likely to have respiratory symptoms when compared to those workers without a history of respiratory illness. This finding is consistent with studies conducted in Ethiopia, Addis Ababa, 24 Komblcha, 9 and Malaysia. 13 In this study, another important factor was washing PPE after use, and respiratory symptoms were higher among workers who did not wash their PPE after use when compared to workers who did wash their PPE after use.…”
Section: Discussionsupporting
confidence: 92%
“…Street sweepers with a history of respiratory illness are more likely to have respiratory symptoms when compared to those workers without a history of respiratory illness. This finding is consistent with studies conducted in Ethiopia, Addis Ababa, 24 Komblcha, 9 and Malaysia. 13 In this study, another important factor was washing PPE after use, and respiratory symptoms were higher among workers who did not wash their PPE after use when compared to workers who did wash their PPE after use.…”
Section: Discussionsupporting
confidence: 92%
“…23 However, another study conducted in Ethiopia found that workers who had ⩾5 years of work experience were less likely to have chronic respiratory symptoms compared to those who had <5 years of work experience. 24 The difference may be due to higher monthly income which means those who had longer work experience also had higher monthly income and could afford materials needed for prevention of chronic respiratory symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory symptoms reported by participants include sore throat, cough, difficulty in breathing, persistent cough, chest pain, chronic mucus, and coughing up blood. Several African studies among municipal solid waste workers [ 32 ], door-to-door solid waste collectors and street sweepers [ 33 ] and landfill waste recyclers [ 34 ], waste workers have reported similar symptoms [ 32 34 ]. Respiratory symptoms generally indicate respiratory disorders including respiratory infections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solid waste motor tricycle operators who use multiple PPE (more than 1 PPE) had lower odds of being infected with a respiratory pathogen. This may be because the components of the multiple PPE have all been shown to confer some level of protection against respiratory infection [ 32 , 42 ].…”
Section: Discussionmentioning
confidence: 99%